Catfish Aquaculture World Enterprise (C.A.W.E.) / Christy Onyo... [et al.] - Onyo, Christy; Ahok, Juliana Apin; Marsuut, Mariana; Saptu, Tracy (2010)
We supplying and selling a good varieties of catfish to all people and who are interested to reared catfish by their own. Catfish Aquaculture World Enterprise (CAWE) is developed because of the higher demand of catfish in Malaysia. This is because Malaysian love to eat fish.They preferred fish more than other meats in the market. Fish is cheaper than other meats. As we know, fish contains high nutrients such as proteins. Plus, catfish is very useful to people. This is because catfish can produce foods and medicine. Besides that, in Mukah area there is still less people doing this business. Therefore, we exist with CAWE to fulfill the demand and market of good varieties of catfish to satisfy our customers.CAWE is in form of partnership between 4 friends. They are graduated from MARA University of Technology (UiTM) with Diploma in Planting Industry Management for 3 years ago. The qualification make them confident to open 2 hectare of Catfish Aquaculture World Enterprise (CAWE) that are located at Jalan Oya, 96400 Mukah. The marketing is focused on Dalat, Matu, Oya, Igan and Mukah. When our company start to growth, we wanted to continue and expand our business to satisfy and fulfil our customers need.Financial analyse show that our company will have both positive cash flow and profit in the first year. We expected that our profit and loss in the first year is 4.55%.